2019
DOI: 10.1088/1361-6463/ab03bb
|View full text |Cite
|
Sign up to set email alerts
|

First principles research on the dynamic conductance and transient current of black phosphorus transistor

Abstract: The validity of high frequency technique and time-domain measurement to nanoscale electronic devices provides an imperious demand to explore the ultrafast electron dynamics and nonlinear responses accompanied with material science in theory. In this work, we carried out a first principles calculation to research the dynamic response in both frequency and time domain of a nanoscale Cu/black phosphorus (Cu/BP) transistor. The system shows n-type transport behaviors due to the charge transfer from the Cu/BP conta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 48 publications
1
4
0
Order By: Relevance
“…Moreover, when the Cu 2+ /Aβ molar ratio was kept constant, Aβ monomers were found to be able to produce more • OH than other forms of Aβ (mainly oligomers and fibrils). These results were consistent with the previous reports in the literature. , The above results clearly demonstrated that the • OH generation via Fenton reaction depended on the Cu 2+ /Aβ molar ratio and the Aβ aggregated states. Notably, the method for • OH production by Cu 2+ –Aβ complex in the presence of AA has been identified in this work (see the Supporting Information (SI), Figure S5).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Moreover, when the Cu 2+ /Aβ molar ratio was kept constant, Aβ monomers were found to be able to produce more • OH than other forms of Aβ (mainly oligomers and fibrils). These results were consistent with the previous reports in the literature. , The above results clearly demonstrated that the • OH generation via Fenton reaction depended on the Cu 2+ /Aβ molar ratio and the Aβ aggregated states. Notably, the method for • OH production by Cu 2+ –Aβ complex in the presence of AA has been identified in this work (see the Supporting Information (SI), Figure S5).…”
Section: Resultssupporting
confidence: 93%
“…The result in Figure S4 indicated that over 82% of BV2 cells were survived with an increase in the fluorescent probe without BP, the cells presented red fluorescence owing to the interaction between Cu 2+ and the fluorescent probe. However, when BP was added and coincubated with cells and the fluorescent probe for a certain time, due to the effective capture of Cu 2+ in the cells by BP, 32,41,42 we observed the disappearance of the red fluorescence (Figure 3A). The same results were acquired for the case of • OH.…”
Section: ■ Results and Discussionmentioning
confidence: 95%
“…Even if a non-interacting description is used for the solution of the relevant Green's functions for the evaluation of transient currents, it is possible to combine the methodology with a predetermined interacting description of the equilibrium state, for example, using DFT-combined modeling. This approach has been taken to study, e.g., gold-fullerene molecular devices [412], hydrogen chains [413], single-electron transistors in the Kondo regime [414], aluminum-carbon molecular devices [393,399,[415][416][417], double-stranded DNA molecules [418,419], magnetic cobalt-graphene and cobalt-copper devices [57,420] (see figure 11(b)), black phosphorus transistors [421], and excitation transport in quasi-one-dimensional quantum devices [422]. It is generally established that the transient signatures follow closely what one would expect from the underlying DFT-resolved electronic band structure even at the SPGF level.…”
Section: Electronic Transportmentioning
confidence: 99%
“…This approach has been taken to study, e.g., gold-fullerene molecular devices [368], hydrogen chains [369], single-electron transistors in the Kondo regime [370], aluminum-carbon molecular devices [348,355,[371][372][373], double-stranded DNA molecules [374,375], magnetic cobalt-graphene and cobalt-copper devices [57,376] [see Fig. 10(b)], black phosphorus transistors [377], and excitation transport in quasi-one-dimensional quantum devices [378]. It is generally established that the transient signatures follow closely what one would expect from the underlying DFT-resolved electronic band structure even at the single-particle Green's function level.…”
Section: Electronic Transportmentioning
confidence: 99%